Combination of amisulpride and olanzapine in treatment-resistant schizophrenic psychoses - Zink, Mathias; Henn, Fritz A.; Thome, Johannes (European psychiatry, 2004)
Treatment-resistant schizophrenia often leads to combined application of antipsychotic drugs. We report first experience with the combination of olanzapine and amisulpride. Improvement of psychopathological state and side effects could be achieved, and drug doses were lower than under monotherapy. We thus conclude that this approach represents a useful therapeutic option.
Gesehen am 03.11.2020